The House of Doors - Tan, Twan Eng (New York : Bloomsbury Publishing, 2023)
"The year is 1921. Lesley Hamlyn and her husband, Robert, a lawyer and war veteran, are living at Cassowary House on the Straits Settlement of Penang. When 'Willie' Somerset Maugham, a famed writer and old friend of Robert's, arrives for an extended visit with his secretary, Gerald, the pair threatens a rift that could alter more lives than one. Maugham, one of the great novelists of his day, is beleaguered: Having long hidden his homosexuality, his unhappy and expensive marriage of convenience becomes unbearable after he loses his savings--and the freedom to travel with Gerald. His career deflating, his health failing, Maugham arrives at Cassowary House in desperate need of a subject for his next book. Lesley, too, is enduring a marriage more duplicitous than it first appears. Maugham suspects an affair, and, learning of Lesley's past connection to the Chinese revolutionary Dr. Sun Yat Sen, decides to probe deeper. But as their friendship grows and Lesley confides in him about life in the Straits, Maugham discovers a far more surprising tale than he imagined, one that involves not only war and scandal but the trial of an Englishwoman charged with murder. It is, to Maugham, a story worthy of fiction"
Keywords: Triangles (Interpersonal relations) -- Fiction; Friendship -- Fiction; Secrecy -- Fiction; Gay men -- Fiction; Married people -- Fiction